High frequency dielectrophoretic response of microalgae over time. Issue 24 (2nd November 2014) - Hadady, Hanieh; Wong, Johnson J.; Hiibel, Sage R.; Redelman, Doug; Geiger, Emil J.; Nilsson, Carol; Lichti, Cheryl; Liu, Huiling
<x xml:space="preserve">Abstract</x> The high frequency dielectrophoresis (>20 MHz) response of microalgae cells with different lipid content was monitored over time. Chlamydomonas reinhardtii was cultured in regular medium and under nitrogen‐depleted conditions in order to produce populations of cells with low and high lipid content, respectively. The electrical conductivity of the culture media was also monitored over the same time. The upper crossover frequency decreased for high‐lipid cells over time. The single‐shell model predicts that the upper crossover frequency is dictated primarily by the dielectric properties of the cytoplasm. The high frequency DEP response of the high‐lipid cells' cytoplasm was changed by lipid accumulation. DEP response of the low‐lipid cells also varied with the conductivity of the culture media due to nutrient consumption. Relative lipid content was estimated with BODIPY 505/515 dye by calculating the area‐weighted intensity average of fluorescent images. Finally, microalgae cells were successfully separated based on lipid content at 41 MHz and DEP media conductivity 106 ± 1 μS/cm.